The Role of Watching TV. in Obesity and Behavioral Problems in Children - B. Seyedamini; A. Moradi; A. Malek; M. Ebrahimi-Mamaghani (Iran University of Medical Sciences, 2010)
Background and Aim: Obesity and overweight as risk factors for many health-related problems have shown an increasing trend in most countries in recent years. Increase in watching television in childhood has been associated with adverse effects on health and behavior in children. Low physical activity due to television viewing is known as a risk factor for childhood obesity. The purpose of this study was to investigate the relatioship between obesity/behavioral problems and television viewing in girls of elementary schools in Tabriz city, Iran.   Matrials and Method: This descriptive comparative study was conducted with a study sample consisting of 300 students girls (7-11 years old) of elementary schools in Tabriz city, selected based on Body Mass Index by stratified random sampling. The data about television viewing were obtained from parent reports using demografic questionnaire and behavioral problems in children were assessed using Child Behavior Check List. Data were analyzed by SPSS software, version 11.5).     Results : The results showed that student girls in overweight and obese groups were viewing television more than those in group of normal Body Mass Index and had lower levels of activity competency.The results suggests a positive and statistical significant association between obesity/overweight and viewing television (r =0.16 ,P<0.005).The children who were viewing television more than 2 houres per day, had a greater Body Mass Index (P<0.011). The length of viewing television had a statistical significant correlation with somatic complaints in children (r =0.153 ,P=0.008).   Conclusion: As watching television for long times is associated with overweighting in children, it is suggested to parents for decreasing television watching time as a preventive method of overweighting.